Explaining Cu@Pt Bimetallic Nanoparticles Activity Based on NO Adsorption - Vines, Francesc; Görling, Andreas (Chemistry - A European Journal, 2020)
Cu@Pt nanoparticles (NPs) are experimentally regarded as improved catalysts for NOx storage/reduction, with higher activities and selectivities compared with pure Pt or Cu NPs, and with inverse Pt@Cu NPs. Here, a density functional theory-based study on such NP models with different sizes and shapes reveals that the observed enhanced stability of Cu@Pt compared with Pt@Cu NPs is due to energetic reasons. On both types of core@shell NPs, charge is transferred from Cu to Pt, strengthening the NP cohesion energy in Pt@Cu NPs, and spreading charge along the surface in Cu@Pt NPs. The negative surface Pt atoms in the latter diminish the NO bonding owing to an energetic rise of the Pt bands, as detected by the appliance of the d-band model, although other factors, such as atomic low coordination or the presence of an immediate subsurface Pt atom do as well. A charge density difference analysis discloses a donation/back-donation mechanism in the NO adsorption.
CRIS-Team Scopus Importer:2020-09-11
Keywords: bimetallic CuPt; core@shell nanoparticles; density functional calculations; electronic structures; NO adsorption